Pengembangan Kompetensi Guru menggunakan Aplikasi Google Classroom pada Masa Pandemic Covid-19 - Nurhijrah; Syarifah Suryana (Jurusan Teknik Informatika dan Komputer, 2020)
The development of teacher competency in using google classroom during the pvidemic covid_19 aims to develop teacher competency in managing online classes using the google classroom application, the method used in this research is the research and development (R&D) method that refers to the ADDIE model with the subject The trial was a teacher at Garudaya Bontonompo Middle School. The results showed an increase in the competency of Garudaya SMKS teachers in using the google classroom application by looking at improvements in each assessment indicator that on average were in the very competent criteria after conducting the pretest and posttest.